SISTEM PENCATATAN RUJUKAN PUSKESMAS DALAM MENINGKATKAN EFISIENSI PELAYANAN KESEHATAN DI DINAS KESEHATAN KABUPATEN BUNGO TAHUN 2025 - Febri Ramanda; Milawati (Jurnal Informatika Medis, 2025)
The referral system is an important component in ensuring effective and efficient health services. In Indonesia, the government has implemented the Integrated Referral Information System (SISRUTE) to facilitate communication between primary health facilities and referral hospitals. This study aims to analyze the referral recording system implemented in community health centers (Puskesmas) and its role in improving health service efficiency at the Bungo District Health Office. The research method used was descriptive analysis through observation, document analysis, and interviews with health office staff responsible for referral reporting. Data were collected from electronic referral records through SISRUTE and manual reports from health centers. The results show that the implementation of SISRUTE has improved the documentation and monitoring of patient referrals. However, several challenges were identified, including limited infrastructure, inadequate internet connectivity, and insufficient technical skills among health workers. The study also found discrepancies between manual and digital referral records in some health centers. Strengthening digital infrastructure, providing regular training for health workers, and developing standardized operational procedures are recommended to optimize the referral recording system. Overall, an integrated referral information system can significantly support the efficiency and coordination of healthcare services.